Danggui Buxue Tang Ameliorates Bleomycin-Induced Pulmonary Fibrosis by Suppressing the TLR4/NLRP3 Signaling Pathway in Rats. (26th July 2021) - Wang, Jiepeng; Wang, Hao; Fang, Fang; Fang, Chaoyi; Wang, Shaoxian; Lu, Chenxi; Liu, Na
Abstract : Objective . To investigate the effects of Danggui Buxue Tang (DBT) on rats with pulmonary fibrosis (PF) and the underlying mechanism. Methods . Sixty specific pathogen-free (SPF) male Sprague-Dawley (SD) rats were randomly divided into 4 groups: control, PF, prednisone treatment, and DBT treatment. Intratracheal instillation of bleomycin (BLM) was performed to establish a PF rat model. DBT was administered to PF rats concurrently for 2 weeks. Lung samples were then collected for HE and Masson staining after pulmonary function testing, and semiquantitative analysis for the degree of alveolitis and fibrosis was performed using the Szapiel and Ashcroft score systems. Myeloperoxidase (MPO) activity, hydroxyproline (HYP), hyaluronic acid (HA), and inflammatory cytokine content were measured. Western blotting was performed to detect fibrotic marker and TLR4/NLRP3 signaling pathway changes. Results . Oral administration of DBT attenuated weight loss, survival rate, and pulmonary index. Lung histopathologic lesions were also reduced. DBT inhibited PF by decreasing the secretion of inflammatory cytokines and collagen deposition. Specifically, DBT reduced tumor necrosis factor-alpha (TNF- α ), interleukin 1 beta (IL-1 β ), IL-6, HYP, alpha-smooth muscle actin ( α -SMA), collagen I, and collagen III levels. Corollary experiments identified a potential mechanism involving suppression of TLR4/MyD88/NF- κ B signaling pathway activation and the NLRP3/ASC/caspase-1 axis, the downstream regulatory pathway. Conclusion . DBT exhibited a potent effect on BLM-induced PF rats by inhibiting the TLR4/NLRP3 signaling pathway. Thus, DBT alleviates pulmonary inflammation to inhibit fibrotic pathology and should be considered as a candidate for the clinical treatment of PF.